Story Mapping Technique And Comprehending Narrative Text - Dian Sartika Simanjuntak; Eka Sustri Harida; Zainuddin Zainuddin (Institut Agama Islam Negeri Padangsidimpuan, 2019)
This research describes about the effect of Story Mapping Technique to comprehend narrative text at grade VIII students of SMP N 5 Padangsidimpuan. There were some problems in this research: 1) The students get difficulties in comprehending the text, 2) The students cannot combine the information that they have already read with their background knowledge, 3) The teacher uses inappropriate technique in teaching reading comprehension. The kind of this research was experimental research. The population of this research was all of the eight grade of SMP N 5 Padangsidimpuan. The total of population were 265 students. Then, the sample of the research was 2 classes, VIII 5 as experimental class that consist of 28 students and VIII 6 as control class that consist of 28 students. The data was derived from pre-test and post-test. To analyze the data, the researcher used t-test formula. Based on the calculation of t-test, the researcher found that tcount = 8.03 and ttable = 1.67356. It means tcount ttable (8.03 1.67356). So, the researcher could concludes that Ha was accepted and Ho was rejected. There was the significant effect of using Story Mapping Technique to comprehend narrative text at grade VIII students of SMP Negeri 5 Padangsidimpuan.